A Simulated Patient Encounter of Status Epilepticus - Joshua Quinones (Association of American Medical Colleges, 2008)
Abstract Introduction Status epilepticus secondary to an isoniazid overdose is life threatening. We created this high-fidelity simulation for emergency medicine residents and medical students to practice the recognition and management of life threatening status epilepticus. Methods This resource includes the stepwise algorithm, environment, lab set-up and values, instructions, and evaluation tools needed to facilitate the simulation. Once learners run through the simulation there is a debrief session using slides and the questions and answers provided. Results Two groups of three residents ran through this case and made the following mistakes: (1) Failure to obtain history of tuberculosis and isoniazid use, and administer pyridoxine; (2) Prolonged time to administer benzodiazepine and phenytoin; and (3) Failure to obtain neurology consult for bedside electroencephalography. Discussion Students adequately performed the majority of the critical actions, but those they missed increased the importance of the debrief session.